LINGUOPRAGMATIC ASPECTS OF MANIPULATIVE STRATEGIES IN THE SPEECH OF THE CHARACTERS OF A. MANZONI “BETROTHED” - Pavliv , Olha (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
In the modern world, manipulation is a completely universal phenomenon. It can be found in all socially significant spheres of human activity. When studying manipulative strategies, it is impossible not to pay attention to the variety of their types and the goals through which manipulators resort to these actions. A set of manipulative techniques organized in a certain way, used for the purpose of exerting hidden influence, aimed at achieving a desired effect or preventing an undesirable result, is presented on examples taken from the historical novel by A. Manzoni "The Betrothed", in particular on the examples of the characters Gertrude, Don Abbondio, Lucia and Renzo. Manipulative strategies are widely used at the level of interpersonal communication. The variety of interpersonal manipulations is analyzed. Regularities between manipulative strategy and stylistic features have been established. In particular, to express the strategy of gaslighting, which is based on contradiction, the author uses affective words, asyndeton, tactics of exaggeration, repetition, and the imperative; to express projection, which consists in transferring one’s responsibility to another person – metaphorical comparisons, antitheses; for the strategy of meaningless conversations, based on monologues that lead to confusion – incomplete sentences, repetitions, asyndeton; for generalization and denigration characterized by vague and abstract statements – incomplete sentences and affective words; to express the strategy of constant disappointment, which is based on the constant disappointment of the manipulator with his victim – asyndeton, exclamations, syntactic parallelism and repetitions. The perlocutionary effect, which is similar in each strategy, was studied. With his non-verbal behavior, the victim tries to convey discomfort and fear: trembling, lowered gaze, and therefore fear to look his manipulator in the eyes, silent submission. At the verbal level, this is manifested by repetitions, incomplete sentences, exclamations, exaggerations and affective words. __________ References: • Bigunova, N. O. «Ilokutyvni cili ta perlokutyvnyj efekt movlennjevogo aktu shvalennja (na materiali anglomovnogo literaturnogo dyskursu)». Naukovyj visnyk Mizhnarodnogo gumanitarnogo universytetu 38 (2019): 55–59. • Gumenjuk, O. Je. Psyhologija vplyvu (Ternopil’: Ekonomichna dumka, 2003), 304. • Zhytnikova, T. A. «Politychne manipuljuvannja: sut’ ta mehanizmy zahystu». Molodyj vchenyj 6 (2014): 620-623. • Zymova, I. A. «Psyhologichna harakterystyka rozuminnja movnogo povidomlennja». Movlennjevyj vplyv u sferi masovoi’ komunikacii’ (1990): 161-169. • Zirka, V. V. Manipuljatyvni igry u reklami: lingvistychnyj aspekt (Dnipropetrovs’k: DNU, 2004), 291. • Zirka, V. V. «Movna paradygma manipuljatyvnoi’ gry v reklami.» (Avtoref. dys. d-ra filol. nauk, Kyi’v, 2005), 34. • Kovalenko, A. M. «Movni zasoby realizacii’ manipuljatyvnogo vplyvu v suchasnyh anglomovnyh ZMI.» Naukovyj visnyk Mizhnarodnogo gumanitarnogo universytetu 38 (2019): 214–218. • Kozak, S. V. «Komunikatyvni strategii’ jak zasib manipuljatyvnogo vplyvu v anglomovnyh pres-relizah». Naukovi zapysky Nacional’nogo universytetu «Ostroz’ka akademija», Serija «Filologichna» 23 (2012): 68–70. • Levchenko, L. O. «Psyhologichni osoblyvosti dijal’nosti zasobiv masovoi’ informacii’». Ljudyna i polityka 2 (2001): 103-108. • Leont’jev, A. A. Osnovy psyholingvistyky (2003), 287. • Megentesiv, S. A., Mohamad, I. Lingvistychni aspekty psyhichnogo vplyvu ta pryjomiv manipuljacii’ (Krasnodar, 1997), 111. • Rizun, V. V., Nepyjvoda, N. F., Kornjejev, V. M. Lingvistyka vplyvu (Kyi’v, 2005), 148. • Ruda, O. G. Movne pytannja jak ob’jekt manipuljatyvnyh strategij u suchasnomu ukrai’ns’komu politychnomu dyskursi (Kyi’v, 2012), 232. • Slovnyk psyhologichnyh terminiv (Kyi’v, Ukrai’na, 2015), https://nuph.edu.ua/slovnik-psihologichnih-terminiv (data zvernennja: 20.02.23). • Tecniche di manipolazione psicologica La mente meravigliosa (Roma, Italia, 2018), https://lamenteemeravigliosa.it/tecniche-di-manipolazione-psicologica/. • Manzoni, A. I promessi sposi, https://it.wikisource.org/wiki/I_promessi_sposi_(Ferrario).